IOT Based Soil Care Solution And Precautions of Seed,food Planting - Pooja Gahile; Sadhana Patekar; Chaitali Meher (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
be solved based on available facts. facts mining strategies are the higher selections for this purpose. Specific facts Mining strategies are used and evaluated in agriculture for estimating the destiny 12 months’ crop manufacturing. therefore we suggest a brief evaluation of crop yield prediction the usage of k Nearest Neighbor (kNN) approach and Density primarily based clustering approach for the selected vicinity i.e. Data mining and gadget getting to know is an rising subject of research in data generation as well as in agriculture. Agrarian zone in India is going through rigorous problem to maximize the crop productiveness. The present observe focuses on the applications of statistics mining techniques in yield prediction in the face of climatic alternate to assist the farmer in taking decision for farming and achieving the predicted monetary return.